Analisis Upaya Kepala Sekoalah Dalam Meningkatkan Kualitas Pembealajaran di SD/MI Kabupaten Kediri - Siti Khomariyah; Moch. Bahak Udin By Arifin (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2025)
First, this research aims to discover the principal principles to improve the learning quality in SD/MI, and second, it will determine the achievement results from the strategies used by school principals to improve the learning quality in SD/MI. Third, to see the problem school principals face to enhance the learning quality in SD/MI. This research used descriptive and qualitative approaches to collect data from interviews, observation, and documentation. The data validity test in this research used data triangulation. This research was conducted at MI Riyadhlatul Uqul Kediri. The results of this research are the strategies used/implemented by the Principal of Mi Riyadhlatul Uqul to improve the learning quality by conducting regular supervision to find out the shortcomings/weaknesses of teachers in the teaching and learning process, the principal implementing teacher capability development by taking part in seminars, training, educational training and also work activities. From the principal, teachers also increase their professionalism in academic institutions. This process brings significant changes in the teaching and learning process, which is innovative, creative, and efficient.